2015
DOI: 10.1002/eji.201545927
|View full text |Cite
|
Sign up to set email alerts
|

5′ and 3′ untranslated regions contribute to the differential expression of specific HLA‐A alleles

Abstract: In hematopoietic stem cell transplantation (HSCT), when no HLA full-matched donor is available, alternative donors could include one HLA-mismatched donor. Recently, the low expressed HLA-C alleles have been identified as permissive mismatches for the best donor choice. Concerning HLA-A, the degree of variability of expression is poorly understood. Here, we evaluated HLA-A expression in healthy individuals carrying HLA-A*02 allele in different genotypes using flow cytometry and allele-specific quantitative RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…In addition, the molecular mechanism underlying HLA expression regulation at the allelic level is far from clear. Although potential mechanisms underlying the regulation of allelic expression at the transcriptional level have been indicated, contradictory conclusions were reached in these studies. To examine how HLA alleles are regulated, analysis of the mRNA level of each allele is essential.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, the molecular mechanism underlying HLA expression regulation at the allelic level is far from clear. Although potential mechanisms underlying the regulation of allelic expression at the transcriptional level have been indicated, contradictory conclusions were reached in these studies. To examine how HLA alleles are regulated, analysis of the mRNA level of each allele is essential.…”
Section: Introductionmentioning
confidence: 95%
“…It has been confirmed that the expression levels of different alleles on the same HLA class I locus can vary dramatically . This differential HLA expression according to alleles could have a broad clinical impact, such as influencing virus infection control, risk of autoimmune disorders, and haematopoietic stem cell transplantation (HSCT) outcomes .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A link between KIR allelic polymorphism and the expression level and/or function of the corresponding KIR + NK cells is necessary for all KIR genes as previously established for the expression level of HLA-A and HLA-Cw molecules (5456). We speculate that KIR allelic polymorphisms may affect not only the distribution and function of these gene products but also the licensing of NK subpopulations as described for HLA class I molecules (57, 58).…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have recently reported variability in the expression of different HLA-C serotypes, as determined at the cell surface or mRNA steady-state levels (58). Variability within HLA-A serotypes has also been recently reported (9). A search for genetic markers of HLA-C expression led to the description of two relevant polymorphisms.…”
Section: Introductionmentioning
confidence: 84%